Pyroelectric Tweezers for Handling Liquid Unit Volumes. (1st July 2020) - Nasti, Giuseppe; Coppola, Sara; Vespini, Veronica; Grilli, Simonetta; Vettoliere, Antonio; Granata, Carmine; Ferraro, Pietro
Abstract : Liquids are the primary environments in which chemical, physical, and biological processes occur. Considering a liquid bridge as liquid unit volume (LUV) element, it is highly desirable to develop reliable tools for handling such volumes. Herein, a sort of intelligent microfluidic platform based on the pyroelectric‐electrohydrodynamics (EHD) is shown for manipulating liquid bridges and thus performing multiple functions in a flexible and simple way. Several basic operations with liquid bridges using an EHD‐pin matrix based on the pyroelectric effect engineered in ferroelectric crystals are demonstrated. By activating pyro‐EHD effect in predetermined positions (pins of the array), the locomotion and handling of single or multiple LUVs simultaneously are controlled. In particular, multiple operations such as lift, displacement, mixing, stretching, and carrying vector for microparticles, are shown. These tweezers based on a pyro‐EHD matrix can open the route for a multipurpose platform driven by physical intelligence and can be used for driving locomotion and operate manifolds functionalities in many areas of science and technology at microscale as well as nanoscale with advantages to be activated by the sole thermal stimulus, controlled remotely, and in noncontact mode. Abstract : An intelligent microfluidic platform, based on pyroelectric‐electrohydrodynamics (pyro‐EHD) is developed for the handling of liquid bridges as liquid unit volume (LUV). Using an array of microelectrodes on the surface of a lithium niobate crystal, individually controlled, the pyroelectric field is generated in different positions attracting the LUV toward the active microelectrode.